EFEKTIVITAS PENERIMAAN PAJAK DAERAH - Mia Febia Rizky, - (2019)
This research is using quantitative study aimed to determine the level of effectiveness of regional tax revenues and to see wether there are infuence of inflation, regional complexity, gross regional domestic product and the number of industries on local tax revenues. This study uses inflation data, population numbers, gross regional domestic products and the number of industries and cities in Central Java Province as a sample. The selection of districts and cities is done through cluster sampling. Testing the hypothesis in the study using Multiple Linear Regression Analysis with SPSS program and a significance level of 5% (0.05). The results of these test indicate that (1) The level of effectiveness of regional tax revenues in Central Java Province in 2013-2017 has an average value of 99.81% which means effective, (2) there is significant negative effect of inflation on local tax revenues, (3) there is no significant effect of population on local tax revenues, (4) there is positive significant effect of gross regional domestic product on local tax revenues, and (5) there is no significant influence on the number of industries to local tax revenues.